Risk factors for graft infection in India: a case-control study. Issue 3 (1st March 2002) - Vajpayee, R B; Boral, S K; Dada, T; Murthy, G V S; Pandey, R M; Satpathy, G
Abstract : Aim: To study the demographic, clinical, and microbiological profile and the risk factors for graft infection following penetrating keratoplasty. Methods: 50 eyes of 50 consecutive patients with graft infection after an optical penetrating keratoplasty were included as cases; 50 eyes of 50 patients with no graft infection were included as controls. The main variables evaluated in this study included the clinical and microbiological profile, sociodemographic status, suture related problems, persistent epithelial defects, and ocular surface disorders. Results: Cultures were positive in 43 (86%) eyes and Staphylococcus epidermidis (67.4%) was the most common organism isolated. Infection could be resolved with treatment in 37 (74%) eyes. In eight (16%) eyes the graft melted and a repeat penetrating keratoplasty had to be performed. Only 6% of the cases could achieve a best corrected visual acuity of 6/18 or better after resolution of the infection. In multivariate logistic regression analysis persistent epithelial defect (OR (95% CI): 3.0 (1.17 to 8.33)), suture related problems (OR (95% CI): 3.6 (1.39 to 9.25)), and ocular surface disorders (OR (95% CI): 2.4 (0.93 to 6.03)) were found to be statistically significant risk factors for graft infection following an optical penetrating keratoplasty. Conclusions: Staphylococcus epidermidis is the commonest organism responsible for post-keratoplasty microbial keratitis. Persistent epithelial defects, suture related problems, and ocular surface disorders are the major risk factors predisposing to graft infection.